(untitled) (Research, Society and Development, 2021)
The Covid-19 pandemic accelerated the adoption of Digital Information and Communication Technologies (TDICs) in the classroom. However, several problems were evident for the students of the so-called Generation C, such as fatigue related to the monitoring of classes through screens of different electronic devices such as: smartphones, tablets, computers (Desktop) and notebooks. And this generation has as one of the characteristics the consumption of content in video format, however, of short duration, objectives, which seek to solve what they are looking for, using mostly mobile devices (smartphones and notebooks). In this work, the focus was to analyze the relationship time x electronic devices in relation to tolerance in the monitoring of classes using two methodologies: video classes and online classes, in addition to realizing which methodology most students of this generation fit. A case study was carried out, applying a questionnaire to students from different courses and levels of education at the Federal Institute of Espírito Santo – Campus Itapina. The results obtained, which were statistically treated, giving greater reliability, showed that the screen size directly influences the tolerance time in following the classes, whether in video classes or as online classes. It is clearly perceived that there is a gap to be filled in the school curriculum regarding the adoption of mobile devices and class planning using this equipment and that take into account the characteristics of students from Generation C.